Crop genetic diversity in the field and on the farm : principles and applications in research practices /: principles and applications in research practices. ([2016]) - Jarvis, Devra I (Devra Ivy), 1959-; Hodgkin, T; Brown, A. H. D; Tuxill, John D; López Noriega, Isabel; Smale, Melinda; Sthapit, Bhuwon
No abstract available